2020
DOI: 10.3389/fnut.2020.00093
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Transgenerational Epigenetic Inheritance of Breast Cancer: The Role of the Paternal Germline

Abstract: The past decade has made evident that in addition to passing their genetic material at conception, parents also transmit a molecular memory of past environmental experiences, including nutritional status, to their progeny through epigenetic mechanisms. In the 1990s, it was proposed that breast cancer originates in utero. Since then, an overwhelming number of studies in human cohorts and animal models have provided support for that hypothesis. It is becoming clear, however, that exposure in the parent generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 90 publications
(197 reference statements)
1
12
0
Order By: Relevance
“…influence the outcome of BCa through transgenerational epigenetic inheritance (da Cruz et al, 2020). The present study evaluated the influence of maternal diet on BCa development in F1 offspring using BALB/c mice and investigated the associated genome-wide epigenetic and transcriptional changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…influence the outcome of BCa through transgenerational epigenetic inheritance (da Cruz et al, 2020). The present study evaluated the influence of maternal diet on BCa development in F1 offspring using BALB/c mice and investigated the associated genome-wide epigenetic and transcriptional changes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Xavier et al (2019) reviewed the impact of various environmental factors, including diets on epigenetic states, and how they can be hereditably transmitted. More precisely, recent evidence has shown that parental diets can influence the outcome of BCa through transgenerational epigenetic inheritance ( da Cruz et al, 2020 ). The present study evaluated the influence of maternal diet on BCa development in F1 offspring using BALB/c mice and investigated the associated genome-wide epigenetic and transcriptional changes.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetics has become a primary research field over the past several years [7]. According to prior research [8], DNA and histone modification are the focuses in epigenetics.…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic patterns are faithfully transmitted between cells during mitotic division, but accumulating evidence suggests that epigenetic information can also be transmitted between generations [17,18]. Accordingly, studies suggest that the progeny's health phenotypes can be acquired in an epigenetically inherited manner due to parental environmental exposures [18,19]. This environmentally induced disease risk has been shown to be transmitted to the offspring via epigenetic mechanisms through both the female and male germ-lines [20][21][22].…”
Section: Of 15mentioning
confidence: 99%
“…Ongoing mouse studies in our lab show that preconception paternal exposure to DDT increases mammary tumorigenesis and tumor aggressiveness in female offspring. The offspring's phenotype is linked to alterations in the sperm small non-coding RNA load of males exposed to DDT [19].…”
Section: Adult Cancersmentioning
confidence: 99%